(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Violence against women is a serious human rights problem that affects people of all racial,ethnic, cultural, and religious backgrounds. It covers any behaviour that, whether in the publicly orprivately domain, might lead to a woman’s death or inflict bodily, psychological, or sexual damage to her.In recent decades, the topic of violence against women has been addressed, argued, advocated for, andbattled for. In addition, extensive research on the prevalence, reporting, and effects of this kind of violenceagainst women has been carried out in several areas and nations. The first proclamation thatacknowledged the need to grant women the principles of equality, security, freedom, integrity, dignity ofall humans was the result of these coordinated activist actions. Despite these international initiativesand the presence of laws that penalise males who assault women, the issue still exists on a global scale.Therefore, in order to tackle the issue at its core, academics believe it is important to identify theunderlying causes motives for such atrocious crimes.